Hubungan Pengetahuan Ibu Tentang Manajemen Laktasi Dengan Pemberian ASI Eksklusif Pada Bayi Usia 6-9 Bulan Di Wilayah Kerja Puskesmas Talang Randai Kabupaten Bengkulu Selatan - Gia Peprianti; Gusni Rahmarianti; Marsimin Marsimin (Jurnal Vokasi Kesehatan, 2022)
The purpose of this study was to determine the relationship between knowledge about lactation management and exclusive breastfeeding for infants aged 6-9 months in the working area of Talang Randai Public Health Center, Bengkulu Selatan Regency. The method in this study is an analytic study with a cross sectional design. The population of this study were all mothers who had children aged 6-9 months in February 2022, totaling 51 people. Data analysis was performed by chi-square test. The results showed that most respondents with less knowledge (41.2%), did not give exclusive breastfeeding (58.8%) and the chi-square test showed X2 count (14.7) > X2 table (5.591) and the value of (0.001)<ρ(0, 05). There is a relationship between knowledge of lactation management and exclusive breastfeeding in the working area of the Talang Randai Health Center, South Bengkulu Regency.